Peran Gender dalam Pengelolaan Budidaya Tanaman Padi Pada Gapoktan Sumber Rejeki Desa Kalanganyar Kecamatan Karanggeneng Kabupaten Lamongan Jawa Timur - PUPUT DEWI PURNAMA; NI WAYAN SRI ASTITI; WAYAN SUDARTA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2017)
Gender Roles in the Management of Rice Cultivation, A Case Study on TheFarmers’ Group of Sumber Rejeki at Kalanganyar Village, Karanggeneng Subdistrict,Lamongan Regency, East Java Most women act as housewives, in addition to being active in household activities,rural women are also participating in rice farming activities from land-processing toharvesting. The study aimed to determine the role of gender in rice farming seenfrom three aspects, namely activity profile, access profile, and control profile(decision making). The research method used is survey method with interviewapproach. Data analysis was conducted descriptivelywith qualitative and quantitativemethods. The findings showed that the role of women and men is different in everyfarming activity. (A) The profile of activity in the outpouring of male labor is greaterthan that of women, the average outpouring of male domestic labor is 199.16 hoursper cultivating season and women is 123.41 hours per season with an average landarea of 6, 64 ares. (B) In the access profile, men have greater access of 78.06% whilewomen of 21.94% ,. (C) The women's participation control profile is very lowcompared with men, it means that the pattern of decision making is dominated bymen up to 96.08%. Based on the results of research, it can be suggested that womenshould play an active role in productive and non productive work. Men are advisedalso to assist in the housework to relieve women's work so that the housework is notneglected. It is also expected to involve women in the extension so that they canincrease participation in their farming activities.